N 6-methyladnosine of vRNA facilitates influenza A virus replication by promoting the interaction of vRNA with polymerase proteins - Qian Wang; Shuai Xu; Wentao Shen; Yanli Wei; Lu Han; Zhengxiang Wang; Yingying Yu; Minxuan Liu; Junwen Liu; Guohua Deng; Hualan Chen; Qiyun Zhu (Proceedings of the National Academy of Sciences, 2025)
N 6-methyladnosine (m 6 A) modification is present in both positive- and negative-strand RNA of influenza A virus (IAV) and affects the replication and pathogenicity of IAV. However, little is known about the regulatory mechanism of m 6 A in IAV RNA. In the present study, we identified the m 6 A methylation of the viral RNA of different IAV subtypes and confirmed that m 6 A modification promotes the polymerase activity and replication of IAV. By mutating m 6 A motifs on the multiple viral RNAs (vRNAs) of IAV, we revealed that m 6 A deficiency in vRNA suppresses the expression of viral genes and the replication of the virus in vitro. In addition, m 6 A deficiency in vRNA reduced the pathogenicity of IAV in a mouse model. Mechanistically, m 6 A deficiency in vRNA suppresses the assembly of the viral ribonucleoprotein (vRNP) complex by impairing the interaction between vRNA and vRNP proteins in an m 6 A methyltransferase-dependent manner, but not the m 6 A reader proteins. Together, our findings reveal an important role for m 6 A on viral RNAs in facilitating the activity of the polymerase complex and the replication and pathogenicity of IAV, which provides insights for the development of novel anti-influenza strategies.